Financial Shenanigans in the Perspective of the Hexagon Theory - Annisa Nurbaiti; Ryan Ramadhan Ferdiawan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Financial Shenanigans are the actions of a person or group in a company by deliberately manipulating the company's financial statements to mislead users of financial statements, one of which is investors. This study aims to see the partial influence of Hexagon Theory on financial shenanigans. The sample of this research is companies in the primary consumer goods sector that are listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used was non-probability sampling and purposive sampling in order to obtain a total of 160 samples from 32 companies in the primary consumer goods sector. The analytical method used is analysis logistic regression and using SPSS 25 software. Based on the results of the entire series of studies conducted, researchers can conclude that, the opportunity variable proxied by the whistleblowing system, the rationalization variable proxied by auditor turnover and the collusion variable proxied by audit fees have no effect on financial shenanigans. Then the variable pressure is proxied by personal financial needs, the variable capability is proxied by the change of directors, arrogance is proxied by the frequency of CEO photos, and has an influence on financial shenanigans. Future research is expected to broaden the scope of data that is the object of research and it is suggested to further test other proxies that represent the Hexagon Theory factors, especially the rationalization, arrogance, and collusion factors and conduct further research on the collusion factor proxied by the audit fee so as to find the results maximum research.